HLA-B27 Negativity Is Associated With Renal Function Decline in Patients With Ankylosing Spondylitis and Secondary IgA Nephropathy - Zhang, Ti; Yang, Fan; Zuo, Ke; Wang, Jinquan; Cheng, Zhen; Zhang, Jiong (Frontiers in Medicine, 2020)
This study aimed to determine the impact of HLA-B27 on the clinical phenotype and renal function during follow-up periods in patients with ankylosing spondylitis (AS) and secondary IgA nephropathy (IgAN). This single-center retrospective study included 71 AS patients with secondary IgAN. Renal function decline was defined as a mean eGFR decline of more than 5 mL/min/1.73 m2 per year or progression into the dialysis stage. The association between the HLA-B27 status and renal function decline was evaluated by univariable and multivariable Cox regression analyses. The results showed that 7 (9.85%) of the 71 included patients were HLA-B27-negative. The median follow-up period was 4.0 years. HLA-B27-negative patients showed higher levels of uric acid (UA) than those who were HLA-B27-positive. Pathologically, a higher percentage of globally sclerotic glomeruli was observed in HLA-B27-negative patients. Survival analysis indicated that HLA-B27 negativity was associated with a significantly higher probability of renal function decline than HLA-B27 positivity. This significant association was also found in subgroup analyses of patients with either substantial proteinuria (more than 1.0 g per day) or interstitial fibrosis and tubular atrophy. Multivariable analysis showed that HLA-27 negativity was independently associated with renal function decline (HR 6.58; 95% CI 1.65 to 26.21; p=0.008). In conclusion, HLA-B27 negativity is associated not only with a higher level of UA and a higher percentage of globally sclerotic glomeruli in AS patients with secondary IgAN but with renal function decline during follow-up periods.